THE LEVEL OF UNDERSTANDING OF GENERAL DOCTORS AND SPECIALIST DOCTORS IN THE MAKING OF VISUM ET REPERTUM IN SEMARANG CITY - Wahyu Purnomo Adji; Intarniati Nur Rohmah; Julia Ike Haryanto; Edward Kurnia Setiawan (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: Visum et repertum is a form of report addressing the condition of human bodies, both living and dead. The reality is that in the field there are still mistakes in making VeR that can influence court decisions, this is also reinforced by the findings of research data that had been done before. Aim: To determine the level of understanding of general doctors and specialists (Obstetrics and Gynecology and Surgery) in making VeR in Semarang City. Methods: Descriptive study of 34 doctors consisting of 16 general doctors, 10 surgeons and 8 obstetricians and gynecologists. The procedure of the research involved collecting data using a questionnaire consisting of the VeR section. The data are sorted according to the group of respondents and description is done. Results: Descriptive analysis showed that the level of understanding of 16 general doctors was categorized as medium with a value of 71.43 % with: 8 doctors (50 %) good questionnaire value, 6 doctors (37.5 %) medium questionnaire value, and 2 doctors (12.5 % ) bad questionnaire value. The level of understanding of 10 surgeons is categorized as good with a value of 76.43 % with: 4 doctors (40 %) good questionnaire value, 6 doctors (60 %) medium questionnaire value, and no bad value. The level of understanding of 8 obstetrics and gynecology specialists was categorized as good with a value of 76.17 % with: 4 doctors (50 %) good questionnaire value, 4 doctors (50 %) medium questionnaire value, and no bad scores. Conclusion: The level of understanding of general doctors was medium with a value of 71.43%, the surgeon specialist was categorized good with a value of 76.43% and obstetricians and gynecology specialists were categorized good with a value of 76.17%.Keywords: level of understanding, visum et repertum